Association of general anesthesia vs procedural sedation with functional outcome among patients with acute ischemic stroke undergoing thrombectomy: a systematic review and meta-analysis - Schönenberger, Silvia; Hendén, Pia Löwhagen; Simonsen, Claus Z.; Uhlmann, Lorenz; Klose, Christina; Pfaff, Johannes; Yoo, Albert J.; Sørensen, Leif H.; Ringleb, Peter A.; Wick, Wolfgang; Kieser, Meinhard; Möhlenbruch, Markus Alfred; et al. (The journal of the American Medical Association, 2019)
Importance General anesthesia during thrombectomy for acute ischemic stroke has been associated with poor neurological outcome in nonrandomized studies. Three single-center randomized trials reported no significantly different or improved outcomes for patients who received general anesthesia compared with procedural sedation. ObjectiveTo detect differences in functional outcome at 3 months between patients who received general anesthesia vs procedural sedation during thrombectomy for anterior circulation acute ischemic stroke. Data Source MEDLINE search for English-language articles published from January 1, 1980, to July 31, 2019. Study Selection Randomized clinical trials of adults with a National Institutes of Health Stroke Scale score of at least 10 and anterior circulation acute ischemic stroke assigned to receive general anesthesia or procedural sedation during thrombectomy. Data Extraction and Synthesis Individual patient data were obtained from 3 single-center, randomized, parallel-group, open-label treatment trials with blinded end point evaluation that met inclusion criteria and were analyzed using fixed-effects meta-analysis. Main Outcomes and Measures Degree of disability, measured via the modified Rankin Scale (mRS) score (range 0-6; lower scores indicate less disability), analyzed with the common odds ratio (cOR) to detect the ordinal shift in the distribution of disability over the range of mRS scores. Results A total of 368 patients (mean [SD] age, 71.5 [12.9] years; 163 [44.3%] women; median [interquartile range] National Institutes of Health Stroke Scale score, 17 [14-21]) were included in the analysis, including 183 (49.7%) who received general anesthesia and 185 (50.3%) who received procedural sedation. The mean 3-month mRS score was 2.8 (95% CI, 2.5-3.1) in the general anesthesia group vs 3.2 (95% CI, 3.0-3.5) in the procedural sedation group (difference, 0.43 [95% CI, 0.03-0.83]; cOR, 1.58 [95% CI, 1.09-2.29];P = .02). Among prespecified adverse events, only hypotension (decline in systolic blood pressure of more than 20% from baseline) (80.8% vs 53.1%; OR, 4.26 [95% CI, 2.55-7.09];P < .001) and blood pressure variability (systolic blood pressure >180 mm Hg or <120 mm Hg) (79.7 vs 62.3%; OR, 2.42 [95% CI, 1.49-3.93];P < .001) were significantly more common in the general anesthesia group. Conclusions and Relevance Among patients with acute ischemic stroke involving the anterior circulation undergoing thrombectomy, the use of protocol-based general anesthesia, compared with procedural sedation, was significantly associated with less disability at 3 months. These findings should be interpreted tentatively, given that the individual trials examined were single-center trials and disability was the primary outcome in only 1 trial.
Gesehen am 28.01.2020